PENGARUH METODE STORYTELLING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X SMK NEGERI 1 LUBUK PAKAM - Hidayah, Tiara; Arianto, Arianto; Muliatik, Sri (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This research aims to determine the effect of the storytelling method in improving the speaking skills of class X students at SMK Negeri 1 Lubuk Pakam. This study involved a random sample of 32 students in the control group and 34 students in the experimental group. The two group pre-test and post-test model was used as the experimental design in this research. Performance tests are used to obtain data. The results of the analysis show that in the control class, the average pre-test score is 58.76, the average post-test score is 61.78, and the standard deviation is 57.96 and 5.73 respectively. In the experimental class, the average pre-test score was 66.88, the average post-test score was 86.93, and the standard deviations were 65.96 and 3.26, respectively. The normality test L_count in the normality test is smaller than L_table (0.2562 < 0.2580) and F_table is smaller than F_table in the homogeneity test, so that the post-test data in both groups is considered normal and homogeneous. With 66 degrees of freedom (n1 + n2 – 2), hypothesis testing is carried out at a significance level of ɑ = 0.05. The null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, because the t_table value is 2.032 and the calculated t_value is 2.933. This proves that there is a significant influence of the storytelling method in improving students' speaking skills.